INTERNAL LOCUS OF CONTROL SEBAGAI PEMODERASI PENGARUH PARTISIPASI PENGANGGARAN TERHADAP SENJANGAN ANGGARAN PADA BANK PERKREDITAN RAKYAT - Pranata, Ngurah Gede Pande hendra; Putri, I G.A.M Asri Dwija (E-Jurnal Akuntansi; Vol 19 No 2 (2017), 2017)
Management participation in the budgeting process tends to cause budgetary slack depending on the interests held by management. The purpose of this study is to determine the effect of budgetary participation on budgetary slack and know the internal locus of control as a moderating variable effect of budgetary participation on budgetary slack. This study was conducted in 35 rural banks in Bali and each Rural Bank taken three respondents. The data used in this study are primary data obtained directly by distributing questionnaires to 105 respondents using purposive sampling technique. Data analysis techniques used in this study are Moderated Regression Analysis (MRA). The results of this study stated that the participation budgeting positive influence on budgetary slack. Internal Lucos of Control can moderate the effect of budgetary participation on budgetary slack.
Keywords: Budgeting Participation, Internal Locus of Control, Budgetary Slack